Let \( p \) represent the price of a peach, and \( a \) represent the price of an apple.
From the information given, we can set up the following two equations based on Mr. Smith's purchases:
-
For the first purchase: \[ 6p + 4a = 13.50 \quad \text{(1)} \]
-
For the second purchase: \[ 4p + 5a = 12.50 \quad \text{(2)} \]
Now, we can solve this system of equations.
First, let's multiply both equations by 2 to eliminate the decimals:
-
Multiply equation (1) by 2: \[ 12p + 8a = 27 \quad \text{(3)} \]
-
Multiply equation (2) by 2: \[ 8p + 10a = 25 \quad \text{(4)} \]
Next, we can eliminate one of the variables. Let's eliminate \( a \) by making the coefficients of \( a \) equal in both equations.
To do this, we can multiply equation (3) by 5 and equation (4) by 4:
-
From equation (3): \[ 60p + 40a = 135 \quad \text{(5)} \]
-
From equation (4): \[ 32p + 40a = 100 \quad \text{(6)} \]
Now we can subtract equation (6) from equation (5): \[ (60p + 40a) - (32p + 40a) = 135 - 100 \] \[ 28p = 35 \] \[ p = \frac{35}{28} = \frac{5}{4} = 1.25 \]
Now that we have the price of a peach \( p = 1.25 \), we can substitute this value back into one of the original equations to find the price of an apple. Let's use equation (1):
\[ 6(1.25) + 4a = 13.50 \] \[ 7.50 + 4a = 13.50 \] \[ 4a = 13.50 - 7.50 \] \[ 4a = 6 \] \[ a = \frac{6}{4} = \frac{3}{2} = 1.50 \]
So, the final prices are:
- The price of a peach ( \( p \) ) is \( $1.25 \).
- The price of an apple ( \( a \) ) is \( $1.50 \).